After the lights go out - Vercher, John (Soho, 2022)
"Xavier "Scarecrow" Wallace, a mixed-race MMA fighter on the wrong side of thirty, is facing the fight of his life. Xavier is losing his battle with chronic traumatic encephalopathy (CTE), or pugilistic dementia--a struggle he can no longer deny. Through the fog of memory loss, migraines, and paranoia, Xavier does his best to keep in shape while he waits for the call that will reinstate him after a year-long suspension. Until then, he watches his diet and trains every day at the Philadelphia gym owned by his cousin-cum-manager, Shot, a retired champion boxer to whom Xavier owes an unpayable debt. Xavier makes ends meet by teaching youth classes at Shot's gym and by living rent-free in the house of his white father, whom Xavier has been forced to commit to a nursing home because of the progress of his end-stage Alzheimer's. Dementia has revealed a shocking truth about Sam Wallace, and Xavier finally gains insight into why his Black mother left the family when Xavier was young. As Xavier battles his aging body and his failing brain, each day is filled with challenges and setbacks. Then Xavier is offered a chance at redemption: a last-minute comeback fight in the largest MMA promotion. If he can get himself back in the game, he'll be able to clear his name and begin to pay off Shot. But with his memory in shreds and his life crumbling around him, can Xavier hold onto the focus he needs to survive? After the Lights Go Out is a haunting, unflinching look at the aftermath of a career in MMA-as Xavier forgets everything around him, you'll want to remember every single word"--